2020
DOI: 10.4067/s0718-381x2020000400602
|View full text |Cite
|
Sign up to set email alerts
|

Paladar o Tuberosidad, ¿Cuál es la Mejor Zona Donadora para un Injerto de Tejido Blando?: Una Revisión Sistemática

Abstract: RESUMEN: Comparar mediante una revisión sistemática los resultados clínicos de los procedimientos de cirugía plástica periodontal/periimplantar (CP) con injerto de tejido blando autógeno (ITB) obtenido del área lateral del paladar (ALP) versus del área de la tuberosidad (AT). Se realizó una búsqueda electrónica de ensayos clínicos en la base de datos Medline/Pubmed, Cochrane y las revistas de Periodoncia e Implantes de mayor impacto según la Web of Science, para hallar artículos publicados hasta abril del 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(20 reference statements)
2
0
0
Order By: Relevance
“…In line with our histological results, recent papers have concluded that although both soft-tissue graft donor areas (lateral palate and tuberosity) yielded similar clinical results, grafting the tuberosity provided greater volume gain and stability of keratinized tissue as well as improved the gingival phenotype of the recipient area (Ramos-Pilco et al, 2020;Rojo et al, 2018Rojo et al, , 2020.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In line with our histological results, recent papers have concluded that although both soft-tissue graft donor areas (lateral palate and tuberosity) yielded similar clinical results, grafting the tuberosity provided greater volume gain and stability of keratinized tissue as well as improved the gingival phenotype of the recipient area (Ramos-Pilco et al, 2020;Rojo et al, 2018Rojo et al, , 2020.…”
Section: Discussionsupporting
confidence: 89%
“…Subepithelial connective tissue grafts from the anterior palate are of looser consistency but can be more extensive, whereas grafts from the posterior palate are usually denser, but limited in size (Sanz et al, 2014). In line with our histological results, recent papers have concluded that although both soft‐tissue graft donor areas (lateral palate and tuberosity) yielded similar clinical results, grafting the tuberosity provided greater volume gain and stability of keratinized tissue as well as improved the gingival phenotype of the recipient area (Ramos‐Pilco et al, 2020; Rojo et al, 2018, 2020).…”
Section: Discussionsupporting
confidence: 89%